KARAKTERISTIK FISIKOKIMIA TEPUNG KULIT PISANG JENIS BANANA - Imelda Yolanda Nayoan; Nurhayati Nurhayati; Puspita Sari (JURNAL AGROTEKNOLOGI, 2014)
Banana is cultivated in Indonesia, classified in two types are plantain and banana. Utilization of the banana peel is still very limited, as animal feed, beside as waste. The purpose of this study were to determine the physicochemical characteristics of banana peels flour (mas, cavendish, barlin and susu variety). This research was condused in two stage, the first stage was banana peel flour production. The second was extraction of banana peel pectin by using water solvent as water soluble pectin (WSP), ammonium oxalate 0,5% solvent as chelating soluble pectin (CSP) and 0,05 M HCl solvent as acid soluble pectin (ASP). The data of the research were analysis by descriptive method presented in table or histogram with error bars or stdev. Physicochemical characteristic of banana peel flour the result showed that physicochemical characteristics were i.e : barlin banana peel flour had moisture content 10,81%, whiteness 67,16%, pectin fraction 0,72% (WSP), 0,78% (CSP), 1,44% (ASP); cavendish banana peel flour had moisture content 12,75%, whiteness 64,37%, pectin fraction 0,78% (WSP), 1% (CSP), 1,72% (ASP); banana peel flour milk had moisture content of 12,73%, whiteness 65,87%, pectin fraction 0,61% (WSP), 0,89% (CSP), 1,50% (ASP); mas banana peel flour had moisture content of 12,38%, whiteness: 66,01 %, pectin fraction 0,56% (WSP), 0,67% (CSP), 1,22% (ASP).Keywords: banana peel flour, physicochemical